2011
DOI: 10.1063/1.3568892
|View full text |Cite
|
Sign up to set email alerts
|

Direct probing of evanescent field for characterization of porous terahertz fibers

Abstract: We develop a technique based on a micromachined photoconductive probe-tip to characterize a terahertz (THz) porous fiber. Losses less than 0.08 cm−1 are measured in the frequency range from 0.2 to 0.35 THz, with the minimum of 0.003 cm−1 at 0.24 THz. Normalized group velocity greater than 0.8, which corresponds to dispersion values in between −1.3 and −0.5 ps/m/μm for 0.2<f<0.35 THz are obtained. Moreover, we directly measure the evanescent electric field as a function of frequency. Good agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Soon thereafter an 871 nm FBG in a TOPAS mPOF was reported and it was demonstrated that the TOPAS FBG was indeed humidity insensitive to within the accuracy of the climate chamber that was used [24]. Interestingly, it has been demonstrated that TOPAS is also a very good material for terahertz (THz) fiber fabrication due to its low material loss and material dispersion at THz frequencies [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Soon thereafter an 871 nm FBG in a TOPAS mPOF was reported and it was demonstrated that the TOPAS FBG was indeed humidity insensitive to within the accuracy of the climate chamber that was used [24]. Interestingly, it has been demonstrated that TOPAS is also a very good material for terahertz (THz) fiber fabrication due to its low material loss and material dispersion at THz frequencies [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…One strategy first demonstrated by Chen et al is to use a subwavelength core surrounded by an air cladding [7,8]. In order to further reduce the loss, a porous structure of sub-wavelength holes can be introduced into the already sub-wavelength solid core of the fiber [10][11][12][13][14][28][29][30], as first predicted numerically by Hassani et al [10,28] and then demonstrated by Dupuis et al [29] and later Atakaramians et al [13]. Due to the boundary conditions in the electric flux density the refractive index step between material and air in the sub-wavelength holes pushes the field into the lower index holes, thereby increasing the fraction of power in air and reducing the absorption losses [30].…”
Section: Introductionmentioning
confidence: 99%
“…Microstructured air-core, solid-core, and porous-core fibers have been extensively studied in the optical domain [15] and have recently become an active field of interest for the guidance of THz waves [6], [7], [ 16 ]- [ 31 ]. Amongst these microstructured fibers, some air-core microstructured fibers stand out as particularly promising [16]- [25].…”
mentioning
confidence: 99%
“…Amongst these microstructured fibers, some air-core microstructured fibers stand out as particularly promising [16]- [25]. A spider-web porous fiber fabricated by extrusion has been demonstrated with loss better than 35 dB/m between 0.2 and 0.35 THz with a minimum loss of 1.3 dB/m at 0.24 THz, but single-mode operation is not claimed in the work [16]. Using 3D printing technology, a hollow core fiber with a triangular-lattice cladding around an air cylinder was demonstrated operating near 0.105 THz with 30 dB/m propagation loss [17].…”
mentioning
confidence: 99%